Elemental iron: reduction of pertechnetate in the presence of silica and periodicity of precipitated nano-structures. Issue 1 (10th December 2020) - Boglaienko, Daria; Qafoku, Odeta; Kukkadapu, Ravi K.; Kovarik, Libor; Katsenovich, Yelena P.; Cherkasov, Denis E.; Emerson, Hilary P.; Levitskaia, Tatiana G.
Abstract : Enhanced TcO4 − reduction by metallic Fe 0 in the presence of particulate and structural Si. Rhythmical precipitation of dissolved iron leads to formation of layered structures related to geological phenomena such as orbicular rocks and Liesegang rings. Abstract : Nano-structural transformation of iron minerals in the natural environment is altered and often retarded in the presence of silica ( e.g., impeded transformation of ferrihydrite) resulting in a modulated interaction with constituents or contaminants present in groundwater. This phenomenon can significantly affect molecular mechanisms of reduction, precipitation, and sequestration of pertechnetate (TcO4 − ), the most prevalent chemical form of radioactive contaminant technetium-99 in the environment, by elemental iron Fe 0 often referred to as zero valent iron (ZVI). Understanding the role of silica in moderating the reactivity of Fe 0 toward reduction of TcO4 − to Tc 4+ and its interaction with in situ formed iron minerals (ferrihydrite, magnetite) is crucial for successful design of a practical separation system and can be related to similar environmental systems. This study was designed to evaluate silica-modified ZVI systems with two commercially available iron materials. The results revealed that the efficiency of TcO4 − reduction by Fe 0 increased in the presence of silica due to inhibited transformation of iron oxyhydroxide into non-stoichiometric magnetite. Moreover, microscopic evaluation of the newly formed iron mineral phases, both in the presence and absence of silica, revealed unique morphologies related to geological phenomena, such as orbicular rocks and Liesegang rings, suggesting that iron dissolution/re-precipitation is a rhythmical reaction–diffusion process, which occurs in both micro-scaled and macro-geological environments resulting in layered structures of iron oxidation products.